2005
DOI: 10.1073/pnas.0509316102
|View full text |Cite
|
Sign up to set email alerts
|

Repression of β-catenin function in malignant cells by nonsteroidal antiinflammatory drugs

Abstract: Activation of the Wnt͞␤-catenin pathway promotes the development of several cancers and is an attractive target for chemopreventive and chemotherapeutic agents. Nonsteroidal antiinflammatory drugs (NSAIDs) have been reported to antagonize ␤-catenin function, but their mechanism of action is not known. We demonstrate here that interference with ␤-catenin function by NSAIDs does not correlate with cyclooxygenase (COX) inhibition. Instead, NSAID inhibition of ␤-catenin requires the high level expression of peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 57 publications
5
62
0
1
Order By: Relevance
“…However, in the presence of a strong PPARg agonist, R-etodolac blocks the recruitment of the coactivator PBP by PPARg. This antagonistic function of R-etodolac was suggested to explain its inhibition of the Wnt/ h-catenin pathway (40). Diclofenac and indomethacin are also NSAIDs capable of both Wnt/h-catenin pathway inhibition and antagonizing strong activation of PPARg (41,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the presence of a strong PPARg agonist, R-etodolac blocks the recruitment of the coactivator PBP by PPARg. This antagonistic function of R-etodolac was suggested to explain its inhibition of the Wnt/ h-catenin pathway (40). Diclofenac and indomethacin are also NSAIDs capable of both Wnt/h-catenin pathway inhibition and antagonizing strong activation of PPARg (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…The direct binding of androgen receptor to h-catenin and Tcf4 is thought to mediate the regulation of Wnt signaling. Like the androgen receptor, PPARg interacts with h-catenin and is found in a complex with Tcf4 (5,40). Thus, it is conceivable that FH535 inhibits a complex containing PPARg h-catenin and Tcf/Lef proteins, depriving the complex bound to Tcf/Lef DNA sites from trans-activating.…”
Section: Discussionmentioning
confidence: 99%
“…18 Easwaran et al found that β-catenin interacts directly with the RAR in a retinoid-dependent manner, but not with the RXR. 16 Recent studies have demonstrated that there was a weak binding between β-catenin and RXRα in HEK293 cells using immunoprecipitation, 15,17 and that β-catenin interacts with PPAR-γ in human malignant cells. 15 However, we used both in vivo mammalian two-hybrid system and in vitro immunoprecipitation approach to detect that there was a direct protein and protein interaction between β-catenin and RXRα neither ligand nor retinoid agonist required, in colorectal cancer cells, which made us further to elucidate the functional regulation and its significance.…”
Section: Discussionmentioning
confidence: 99%
“…10 Therefore, targeting β-catenin is a promising strategy for cancer prevention and chemotherapy via suppressing β-catenin by nonsteroidal anti-inflammatory drugs (NSAIDs), [11][12][13][14] which required high level expression of PPARγ and RXRα. 15 It has been reported that RAR interacts with β-catenin and inhibits β-catenin-mediated gene transcription. [16][17][18] But, whether there is an interaction and what is the functional regulation between RXRα and β-catenin are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…3 SDX-308 (CEP-18082), a novel analog of etodolac, has more potent cytotoxicity than R-etodolac in several cancer cell lines including colon, prostate, ovarian and breast cancer, Recent studies have shown that NSAIDs including R-etodolac inhibit b-catenin-dependent transcription in malignant cells; however, its mechanisms of action has not yet been fully defined. [4][5][6][7] Specifically, the colonic polyps of patients treated with NSAIDs have reduced nuclear accumulation of b-catenin. 5 b-catenin/T-cell factor (TCF) signaling is known to regulate developmental processes and can lead to malignant transformation via upregulation of its target genes 8,9 including c-myc, 10,11 survivin, 12,13 and cyclin D1 14 associated with MM cell growth and survival.…”
Section: Introductionmentioning
confidence: 99%